Direct glucose sensing and biocompatible properties of a zinc oxide – multiwalled carbon nanotube–poly(vinyl chloride) ternary composite. Issue 12 (10th March 2016) - Manikandan, Palinci Nagarajan; Imran, Habibulla; Dharuman, Venkataraman
Abstract : Zinc oxide (ZnO), multi-walled carbon nanotubes (functionalized: fMWCNT and purified: pMWCNT), and poly(vinyl chloride) (PVC) (PVC–ZnO–MWCNT) are used for fabricating a ternary biocompatible composite on a glassy carbon surface for direct glucose sensing. Abstract : Zinc oxide (ZnO), multi-walled carbon nanotubes (functionalized: fMWCNT and purified: pMWCNT), and poly(vinyl chloride) (PVC) (PVC–ZnO–MWCNT) are used for fabricating a ternary composite on a glassy carbon surface for direct glucose sensing. Enhanced glucose sensing is noticed with the PVC–ZnO–pMWCNT ternary composite in neutral (7.4) pH rather than in acid and alkaline pHs and not with the PVC–ZnO–fMWCNT and PVC–ZnO–MWCNT composites. The reasons for the highest activity of the PVC–ZnO–pMWCNT are examined using cyclic voltammetry (CV), chronoamperometry (CA), flow injection analysis (FIA), quartz crystal microbalance (QCM), Scanning Electron Microscopy (SEM), Fourier Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Raman spectroscopic and Transmission Electron Microscopic (TEM) techniques. The results suggest more interactions of ZnO with the pMWCNT rather than with the fMWCNT and MWCNT in the presence of PVC. Excellent selectivity of glucose in the presence of potential interferences, biocompatibility in the presence of blood proteins (bovine serum albumin and bilirubin) and antibacterial ( Staphylococcus aureus and Keblisa pneumonia ) activities are observed for ZnO in the presence of the MWCNT and PVC. The PVC–ZnO–pMWCNT composite shows the highest Michaelis–Menten kinetic constant k M of 21.9 mM compared to ZnO–glucose oxidase and copper oxide–ZnO systems which exhibit 10 times lower k M values. Blood glucose in different diabetic persons is discriminated very well without affecting the sensor performance.